Early Nasogastric Tube Removal After Abdominal Aortic Surgery - Cameron, Diane; Lovell, Marge; Jamieson, W. G. (Operating Room Nurses Association of Canada Journal, 1992)
Controversy exists concerning the length of time that nasogastric tube drainage is necessary after abdominal aortic surgery. The purpose of the tube is to reduce gastrointestinal distention, prevent gastric dilatation and potential respiratory complications. Classic surgical teaching suggests that the tube not be removed until bowel sounds are present and or the patients have passed ﬂatus. This classic teaching is now challenged. This study was conducted to determine the need for routine prolonged nasogastric decompression following aortic surgery.